HUBUNGAN PEMASANGAN IUD POST PLASENTA DENGAN KEJADIAN EKSPULSI PADA WANITA USIA SUBUR - Fuadah, Linatul; Kumalasari, Retno (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
The insertion of IUD post plasenta has the benefit but it also has a weakness. The meakness is the failure still hight, it is because the insertion is done when the uterus condition still wide. IUD could be pushed out when the size ofe uterus back to the original size. The amount of expulsion case can be failed. Ekspulsion care usually accures at the age of the first 3 months after insertion. The aim of this reaserch is to know the relationship of the IUD post plasenta insertion with the ekspulsion care at WUS in public health center bobotsari purbalingga regency in 2013. The design used in the research is descriptive analitic. The population in this research is WUS who use IUD post plasenta period 1 Januari-31 march 2013 are 32 women.Â  The sampe used is total sampling. Statistic analisis used chi square. Based on the research, there are 32 respondences IUD post placenta. most of them succesed, 24 women based on chi square test it is gained, p value = 0,005 and Î± = 0,05 so there is the relationship between the insertion of IUD post placenta with the ekspulsion case at WUS in public health center bobotsari purbalingga. Keyword : IUD post placenta, ekspulsion